Predictors of faculty narrative evaluation quality in medical school clerkships. Issue 12 (23rd August 2022) - Mooney, Christopher J.; Pascoe, Jennifer M.; Blatt, Amy E.; Lang, Valerie J.; Kelly, Michael S.; Braun, Melanie K.; Burch, Jaclyn E.; Stone, Robert Thompson
Abstract: Introduction: Narrative approaches to assessment provide meaningful and valid representations of trainee performance. Yet, narratives are frequently perceived as vague, nonspecific and low quality. To date, there is little research examining factors associated with narrative evaluation quality, particularly in undergraduate medical education. The purpose of this study was to examine associations of faculty‐ and student‐level characteristics with the quality of faculty member's narrative evaluations of clerkship students. Methods: The authors reviewed faculty narrative evaluations of 50 students' clinical performance in their inpatient medicine and neurology clerkships, resulting in 165 and 87 unique evaluations in the respective clerkships. The authors evaluated narrative quality using the Narrative Evaluation Quality Instrument (NEQI). The authors used linear mixed effects modelling to predict total NEQI score. Explanatory covariates included the following: time to evaluation completion, number of weeks spent with student, faculty total weeks on service per year, total faculty years in clinical education, student gender, faculty gender, and an interaction term between student and faculty gender. Results: Significantly higher narrative evaluation quality was associated with a shorter time to evaluation completion, with NEQI scores decreasing by approximately 0.3 points every 10 days following students' rotations ( p  = .004). Additionally, women faculty had statistically higher quality narrative evaluations with NEQI scores 1.92 points greater than men faculty ( p  = .012). All other covariates were not significant. Conclusions: The quality of faculty members' narrative evaluations of medical students was associated with time to evaluation completion and faculty gender but not faculty experience in clinical education, faculty weeks on service, or the amount of time spent with students. Findings advance understanding on ways to improve the quality of narrative evaluations which are imperative given assessment models that will increase the volume and reliance on narratives. Abstract : With the field's increased reliance on narrative‐based assessment, @mooneymed and colleagues examine predictors of faculty narrative evaluation quality in clinical clerkships. #URResearch #Meded